2019
DOI: 10.12669/pjms.35.4.753
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian reserve parameters and response to controlled ovarian stimulation in infertile patients

Abstract: Objective: To determine the ovarian reserve parameters in patients presenting for IVF and intracytoplasmic sperm injection (ICSI) treatment and its association with the number of follicles retrieved and number of oocyte retrieved and fertilized. Methods: A retrospective cross sectional study was conducted at Australian Concept Infertility Medical Centre from January 2017 to August 2017. Around 120 couples presenting to infertility clinics selected for IVF and ICSI with Females (25-45) had their FSH, AMH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…The present study revealed a gradual decrease of AFC, AFC/age ratio, AMH/age ratio, and ORPI with increase in age of female where decrease in AMH was significant between groups 1, 2, and 3. The decreasing trend of aforementioned four variables is consistent with previous studies [ 4 , 20 , 29 ] and could accurately reflect the diminished status of ovarian reserve of infertile women with ageing. However, the trend of traditional predictors such as FSH, LH, E2, and FSH/LH ratio was not developed in this study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The present study revealed a gradual decrease of AFC, AFC/age ratio, AMH/age ratio, and ORPI with increase in age of female where decrease in AMH was significant between groups 1, 2, and 3. The decreasing trend of aforementioned four variables is consistent with previous studies [ 4 , 20 , 29 ] and could accurately reflect the diminished status of ovarian reserve of infertile women with ageing. However, the trend of traditional predictors such as FSH, LH, E2, and FSH/LH ratio was not developed in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The reliable markers of ovarian reserve provide an accurate estimation of NOR and GQE in the IVF/ICSI cycles of infertile women. The markers of diminished ovarian reserve and poor ovarian response, including female age, basal serum follicle-stimulating hormone (FSH), estradiol (E2), anti-Müllerian hormone (AMH), inhibin B, antral follicle counts (AFC), and ovarian volume, are used in ovarian stimulation during IVF/ICSI [ 2 4 ]. Usually, basal serum FSH level at day 3 was used to predict ovarian reserve, and level >10 IU/liter was considered consistent with poor ovarian response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AMH is a glycoprotein secreted by granulosa cells of developing ovarian follicles (Siddiqui et al, 2019). It is involved in folliculogenesis and reflects the number of primordial follicles (Seifer & Maclaughlin, 2007;Pellatt et al, 2010;Tobler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%